DEALING WITH CULTURAL CLASHES - Qodirov Halillullo; Rahimova Feruza Baxtoyorzoda kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article describes the causes of intercultural conflict and its types. In addition, the views of scientists about wars between cultures in the future are alsocovered.